PENGEMBANGAN POTENSI EKONOMI DAN PENETAPAN SEKTOR UNGGULAN DI PROVINSI JAWA TIMUR WILAYAH UTARA - Reza Aditama (Media Ekonomi, 2018)
This research aims to look at the economic potential and determination of superior sectors in the eastern Java province of the north. This research uses the Klassen Typology, Location Quotient, and Shift Share analysis with the help of Microsoft Excel 2013 analysis tool. The data used in this study are East Java Province GRDP Growth Rate, GRDP Growth Rate and GDP per capita in East Java Province in the period 2012 to 2016. The results of the Klassen Typology analysis show that there are in quadrant 1, Bojonegoro district, 2 districts are in quadrant 3 namely Lamungan and Sumenep districts, and there are 5 districts in quadrant 4 namely Tuban district, Ngawi district, Bangkalan district, Sampang district, Sumenep district . In the LQ Analysis results are obtained about the sectors that become the base sector. The result is that Lamungan district has 10 base sectors, Bojonegoro district has 4 base sectors, Tuban district has 7 base sectors, Ngawi district has 5 base sectors, Bangkalan district has 6 base sectors, Sampang district has 4 base sectors, Pamekasan district has 8 sectors base, Sumenep district has 3 base sectors. Furthermore, from the Shift Share analysis, the results of the competitive sector and growing faster than the reference region, namely East Java, namely Lamungan district has 8 sectors, Bojonegoro district has 6 sectors, Tuban district has 7 sectors, Ngawi district has 7 sectors, Bangkalan district has 6 sectors , Sampang district has 7 sectors, Pamekasan district has 7 sectors, Sumenep district has 6 sectors.